Canh Tác Nông Lâm Kết Hợp Bền Vững Cho Vùng Trung du, Miền Núi Phía Bắc - National Agricultural Extension Center (World Agroforestry Centre, 2021)
The upland areas of Northwest in Viet Nam are home to ethnic minorities with high poverty prevalence. Low access to markets and cash for investments limit sustainable livelihood development. Steep mountain slopes are exploited for agriculture which leads to erosion and soil degradation, and to low yields and profitability of agriculture. Agroforestry is suggested to mitigate these challenges, improve food security and aid in climate change mitigation and adaptation. ‘Sustainable agroforestry cultivation for the Northern Midlands and Mountainous area’ provides readers with basic knowledge and introduces new technical advances in agroforestry that can be applied to sustainable agriculture on sloping land.